2012
DOI: 10.1177/0037549712450532
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis and simulation of pedestrian evacuation under invisible conditions

Abstract: We study a class of pedestrian evacuation process in rooms without visibility by analytical and simulative methods. First, the moving distance of pedestrians for leaving the rooms is analyzed using the mean and variance theory. A microscopic pedestrian model is then extended to simulate pedestrian evacuation in the rooms. By numerical examples, the distributions of single individual's evacuation efficiency in the rooms and the improvement by increasing the number of exits for the individual's evacuation effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…W. J. Yu et al [2] proposed a centrifugal force model based on pedestrian behavioural simulation and pedestrian dynamics to study the pedestrian traffic characteristics. In addition, some scholars analysed the path selection behaviour of pedestrians inside a large building [3], and then constructed a dispersive pedestrian microscopic simulation model [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…W. J. Yu et al [2] proposed a centrifugal force model based on pedestrian behavioural simulation and pedestrian dynamics to study the pedestrian traffic characteristics. In addition, some scholars analysed the path selection behaviour of pedestrians inside a large building [3], and then constructed a dispersive pedestrian microscopic simulation model [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that, compared with blind random movement, blind following movement could reduce the blindness of moving targets and directions to a certain extent. Guo et al carried out the classroom evacuation experiment in the case of good visibility and zero visibility [4] and found several pedestrian walking characteristics without guidance [5]. Cao et al [6, 7] carried out the pedestrian evacuation experiment in the area without obstacles under the condition of a completely limited visual field and established the pedestrian walking model without guidance.…”
Section: Introductionmentioning
confidence: 99%
“…These behaviors are critical in reflecting the characteristics of the pedestrian evacuation process under adverse sight conditions. Based on the degree of the adverse sight condition, research in pedestrian evacuation has mainly been carried out from two aspects: pedestrians without visibility [15][16][17][18][19][20] and pedestrians with a sight radius. [21][22][23][24][25] Under the condition without visibility, since the visible scope of pedestrian evacuation is completely affected, blind and disoriented pedestrians cannot acquire and recognize the information from evacuation surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…Nagai et al 17 studied the effect of the configuration of exits in a dark room without visibility on the evacuation process. Guo and Huang 18 investigated pedestrians' moving distances during evacuation from a room without visibility by analytical and simulative methods, in which the improvement of an individual's evacuation efficiency was demonstrated by increasing the number of exits. Guo et al 19 investigated the route choice of pedestrians evacuating from a classroom with internal obstacles and zero visibility using experiments and microscopic simulations, in which evacuation exercises were concluded to be helpful for improving the efficiency of pedestrian evacuation under the condition of zero visibility.…”
Section: Introductionmentioning
confidence: 99%